The role of school performance in narrowing gender gaps in the formation of STEM aspirations: a cross-national study - Mann, Allison; Legewie, Joscha; DiPrete, Thomas A. (Frontiers in Psychology, 2015)
Abstract This study uses cross-national evidence to estimate the effect of school peer performance on the size of the gender gap in the formation of STEM career aspirations. We argue that STEM aspirations are influenced not only by gender stereotyping in the national culture but also by the performance of peers in the local school environment. Our analyses are based on the Program for International Student Assessment (PISA). They investigate whether 15-year-old students from 55 different countries expect to have STEM jobs at the age of 30. We find considerable gender differences in the plans to pursue careers in STEM occupations in all countries. Using PISA test scores in math and science aggregated at the school level as a measure of school performance, we find that stronger performance environments have a negative impact on student career aspirations in STEM. Although girls are less likely than boys to aspire to STEM occupations, even when they have comparable abilities, boys respond more than girls to competitive school performance environments. As a consequence, the aspirations gender gap narrows for high-performing students in stronger performance environments. We show that those effects are larger in countries that do not sort students into different educational tracks.